(untitled) (International Journal of Innovative Technologies in Economy, 2019)
Earth is continents, seas, the developing countries, the developed countries, the centers and the borders is the One Belt-One Road initiative. On the other hand, the Sea “Silk Road” is called the “Economic Belt of the Silk Road” as a way of “New Belt and Road” for China’s new long-term development strategy. "Silk Road" refers to the ancient land-based commercial trade route that originated in ancient China and connected to Asia, Africa and Europe. In order to benefit from the “Economic Belt of the Silk Road” initiative, China has partnered with other Asian countries and created two important financial development institutions, the Asian Infrastructure Investment Bank and the Silk Road Fund. The main objective of the initiative is to create an Eurasian trade economic integration space and cross-border transport corridors, that is, to strengthen the links between government policies and national development strategies along the route, promote international cooperation, and promote the development of joint ventures. For this purpose, the following tasks have been set: 1. Development of regional economic integration method; 2. Create an integrated transportation design for Asian transportation, connect communication networks, and develop pipeline systems; 3. Switch back to investment and trade barriers and create a good investment environment; 4.Strengthen national currency; 5.Deepening cooperation in the humanitarian field; 6.Expanding China’s exports and domestic power growth will be concentrated in the western provinces (steel, lead, photovoltaic equipment, wind turbines). The “One Belt and One Road” is a new starting point for China-global relations and human development. Utilize the geographical advantages of Mongolia, China and Russia to increase cross-border trade between Mongolia, Russia and China, creating opportunities for logistics and transportation. China is one of the Mongolia’s largest sources of foreign direct investment and is seen as a huge market for Mongolia to provide services and products. Mongolia hopes to unite its “Steppe Road” initiative with China’s “One Belt and One Road” initiative. The goal of the “Steppe Road” initiative aims to expand the Mongolian economy through cross-border transportation, strengthen the road line connecting Russia and China, transform and extend the current railway line in Mongolia, and build oil and gas between Russia and China. The pipeline improves the infrastructure of Mongolia. Mongolia and other Asian countries are actively participating in the “One Belt and One Road” initiative implemented in China to reduce risks and threats and gain new opportunities and advantages in regional cooperation.